Electrocatalytic desalination with CO2 reduction and O2 evolution. Issue 28 (8th July 2021) - Shen, Kaixiang; Wei, Qiang; Wang, Xin; Ru, Qiang; Hou, Xianhua; Wang, Guannan; Hui, Kwan San; Shen, Jiadong; Hui, Kwun Nam; Chen, Fuming
Abstract : An electrocatalytic desalination device exhibits a quick removal rate with formate generation at the cathode and oxygen evolution at the anode. Abstract : Multifunctional electrocatalytic desalination is a promising method to increase the production of additional valuable chemicals during the desalination process. In this work, a multifunctional desalination device was demonstrated to effectively desalinate brackish water (15 000 ppm) to 9 ppm while generating formate from captured CO2 at the Bi nanoparticle cathode and releasing oxygen at the Ir/C anode. The salt feed channel is sandwiched between two electrode chambers and separated by ion-exchange membranes. The electrocatalytic process accelerates the transportation of sodium ions and chloride ions in the brine to the cathode and anode chamber, respectively. The fastest salt removal rate to date was obtained, reaching up to 228.41 μg cm −2 min −1 with a removal efficiency of 99.94%. The influences of applied potential and the concentrations of salt feed and electrolyte were investigated in detail. The current research provides a new route towards an electrochemical desalination system.